Penerapan Model Pembelajaran Snowball Throwing dalam Meningkatkan Hasil Belajar Peserta Didik Mata Pembelajaran PAI di SMPN 23 Konawe Selatan - Aris Try Andreas Putra; Sufiani Sufiani (Universitas Alma Ata, 2021)
This study aims to describe the application of the snowball throwing learning model in improving the learning outcomes of students in Islamic religious education subjects in class VIII 2 at SMP Negeri 23 Konawe Selatan. This type of research is a classroom action research (PTK) with research procedures in two cycles with several stages, namely planning, action, observation and reflection. The data collection techniques used were observation, test learning outcomes and documentation. Observations were made to determine the activities of researchers and students in implementing learning. Learning outcome tests are carried out to determine the completeness of student learning outcomes. Meanwhile, documentation is used to obtain data about the state or number of students who will be studied in class VIII 2 SMP Negeri 23 Konawe Selatan. From the results of the study, students who scored above 70 in the pre-cycle initial test were 5 people with an average of 59.14 and a percentage of 23, 80%. After the implementation of cycle I, 11 students who achieved mastery learning above a value of 70 with an average score of 63.80 and a percentage of 52.38%. Furthermore, after the implementation of cycle II, 17 students who obtained a value of 70 and above with an average of 71.90 and a percentage of 80.95%.